The impact of colonial taxation system in Chirumanzu district from 1900- 1980. - Magwarada, Michael F. T. (Midlands State University, 2017)
The period between 1900-1980 witnessed effective occupation by the colonialists administration in Rhodesia. The colonial regime imposed potentate rule through their introduction of the colonial taxation system on black people in Chirumanzu district. The plight of black people in Chirumanzu district towards the impact of colonial taxes has been largely ignored by post-colonial historians. In this study l take perspective to primarily focus on how black people were exposed to deplorable conditions coupled with their reactionary tendencies as an impact of the colonial taxation system mainly in Chirumanzu district and partially Zimbabwe. Generally this study argues that in Chirumanzu reserve the colonial taxation system infringed black people rights and further acted as a blockade to their economic development whilst favouring more profits towards the white community. Laws such as the Masters and Servants Ordinance of 1901 which made it a criminal offence to break a labour contract, and denying favourable markets for African produce among many others were imposed on Africans so as to secure cheap labour and achieve the settlers’ main goal of making immense profits in Rhodesia. The colonial taxation system in Chirumanzu district was “a great vampire squid, wrapped around the face of humanity”. This study also argues that colonial taxes were an emotional and sensitive issue to black people in Chirumanzu since they were taxed from domestic animals to property, personal belongings and almost everything. It cornered Africans to the point of formulating resistance. Methodologically this study depends on primary sources in form of oral testimonies and also written sources with original pictorial evidence.